A Study of the Fair trade Business model in the UK and its applicability in Japan - Shibahara, Aki (2007)
This project seeks to analyse the fair trade business model in the UK and explore its applicability to Japan. The research questions are: what are the competitive advantages of the fair trade business, why are UK fair trade companies commercially viable, and whether the UK fair trade business model is applicable to the Japanese market.